Control system design of a highly-extensible soft continuum robot - Talaş, Şeref Kemal. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
In this thesis, control system design of a highly-extensible soft robot is presented. The robot is actuated with three inﬂatable tubings connected to stepper motors and can move in three-dimensional space. Pressurizing the tubings provides the body stiﬀness and creates a thrust at the end-eﬀector to move the robot, whereas position and speed of the tubings are controlled by the stepper motors. Control system includes open-loop speed and position controllers. Also, a teleoperation controller is designed to move the robot by user input from a commanding device. The speed controller is designed only for straight extension and contraction, and it does not provide a three-dimensional speed control. The position controller moves the robot tip to the desired real-world coordinates in three-dimensional space. Finally, the teleoperation controller is used to control the extension/contraction speed and to steer the robot by diﬀerentiating the speed of three tubings depending on the user input. The robot is subjected to tests in free-space to measure the accuracy of the speed and position controllers. The teleoperation controller is also tested using the commanding device in order to check whether it is possible to move the robot tip to a target in free-space, through obstacles, and in an enclosed environment. All of the controllers are validated by the experiments. Considering the test results, the proposed highly-extensible soft continuum robot and the designed controllers are promising for many applications such as inspection, urban search and rescue, and minimally invasive surgery.
Keywords: Robots -- Control systems.; Adaptive control systems.